End-stage coxarthrosis and gonarthrosis. Aetiology, clinical patterns and radiological features of idiopathic osteoarthritis. - Chitnavis, J; Sinsheimer, J; Suchard, M; Clipsham, K; Carr, A (2000)
OBJECTIVES: To determine and compare the aetiological background, clinical patterns and radiological features of idiopathic osteoarthritis (OA) of the hip and the knee warranting arthroplasty. METHODS: A total of 402 Caucasians consecutively undergoing total hip replacement (THR) or total knee replacement (TKR) for idiopathic OA at a major centre was surveyed. RESULTS: Previous joint injury was more common in the TKR group (P < 0.0001). However, both groups manifested a mixed occupational background, body mass indices similar to the general population and a predominance of females (F:M = 1.3-1.4:1). The TKR group had a significantly younger age of symptom onset (56 yr) than the THR group (61 yr) but both groups had a tendency to bilateral arthroplasty (33%), nodal involvement (54-59%), a significant excess of right-sided replacements (1.8:1, THR; 2.2:1, TKR) and similar levels of pre-operative pain and disability. Up to 40% of hips manifested acetabular dysplasia and 10% possible previous slipped upper femoral epiphyses. Eighty-five per cent with end-stage coxarthrosis or gonarthrosis had an identical pattern of radiographic disease contralaterally. CONCLUSIONS: Our data suggest the importance of a constitutional tendency to idiopathic, end-stage OA, a disorder traditionally associated with environmental factors leading to 'wear and tear'.